Early Seizure Recurrence in Children Admitted for Nonfebrile Seizures in the Emergency Department: A Prospective Study - Ropars, Juliette; Sacaze, Elise; Abalea, Lydie; Peudenier, Sylviane; Vic, Philippe; Lemoigno, Laurence; Dailland, Thomas; Courgeon, Lisa; Lefranc, Jeremie (Neuropediatrics, 2022)
Objective This study was aimed to determine the rate, timing, and risk factors of acute recurrence of seizures in the children admitted for nonfebrile seizure in the emergency department (ED).Methods This multicenter prospective study was conducted in the ED of three hospitals. All consecutive visits of children aged 28 days to 15 years who attended the ED for a nonfebrile seizure for 1 year were included in the study and prospectively followed. The rate of acute seizure recurrence within 24 hours was evaluated and association with potential risk factor was tested. Timing of seizure recurrence was assessed.Results A total of 181 ED visits were enrolled. Overall, 19.9% (36/181) of children presented acute seizure recurrence, 50% of seizure recurrence occurred during the 2 hours after ED arrival and 70% within 6 hours. Multivariable analysis showed that age of <5 years and seizure recurrence in the emergency department were associated with a significant increase in acute recurrence risk.Conclusion Early seizure recurrence is common in children with nonfebrile seizure, with younger children at higher risk. Based on these findings, acute recurrence risk after a nonfebrile seizure should justify to observe the children admitted for a nonfebrile seizure in the ED, especially young children. A larger study should analyze other risk factors associated with increased risk of acute seizure recurrence and help ED management.
Keywords: seizure recurrence; nonfebrile seizure; emergency department